2001
DOI: 10.1074/jbc.m008869200
|View full text |Cite
|
Sign up to set email alerts
|

Protein-tyrosine Kinase Pyk2 Mediates Endothelin-induced p38 MAPK Activation in Glomerular Mesangial Cells

Abstract: Endothelin-1 (ET-1), a member of a family of 21 amino acid peptides possessing vasoconstrictor properties, is known to stimulate mesangial cell proliferation. In this study, ET-1 (100 nM) induced a rapid activation of p21 ras activation and suggested the involvement of the cytoplasmic proline-rich tyrosine kinase Pyk2. We have observed that Pyk2 was expressed in HMC and was tyrosine-phosphorylated within 5 min of ET-1 treatment. ET-1-induced activation of Pyk2 was further confirmed using phospho-specific anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 59 publications
9
64
4
Order By: Relevance
“…Our results confirm earlier studies (15,(17)(18)(19)(20) and indicate that CRNK indeed functions as a dominant-negative inhibitor of PYK2 in cardiomyocytes. CRNK prevented PYK2 autophosphorylation at Y 402 in response to both ET and H 2 O 2 treatment of NRVM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results confirm earlier studies (15,(17)(18)(19)(20) and indicate that CRNK indeed functions as a dominant-negative inhibitor of PYK2 in cardiomyocytes. CRNK prevented PYK2 autophosphorylation at Y 402 in response to both ET and H 2 O 2 treatment of NRVM.…”
Section: Discussionsupporting
confidence: 92%
“…A replication-deficient Adv encoding FLAG-tagged, human CRNK (Adv-CRNK) was kindly provided by Dr. Andrey Sorokin, Medical College of Wisconsin (18). An Adv expressing GFP (Adv-GFP) was used to control for nonspecific effects of Adv infection (23).…”
Section: Adenoviral Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyk2 signaling has been implicated in the activation of the ERK, JNK and p38MAPK pathways Tokiwa et al, 1996;Blaukat et al, 1999;Sorokin et al, 2001). Direct association of Src kinases with Pyk2 is essential for engaging the ERK/MAPK cascade (Blaukat et al, 1999;McMullen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that activation of Pyk2 was necessary for the activation of ERKs and/or SAPKs in different cell lines and in response to various stimuli (47)(48)(49)(50)(51)(52). Thus, it was of interest to determine whether the inhibition by s-FKN of MCP-1-induced p38/SAPK2 activity, which leads to the abrogation of MCP-1-induced chemotaxis of MonoMac6 cells, was associated with an inhibition of Pyk2 activity.…”
Section: S-fkn Abrogates the Mcp-1-induced Activation Of Pyk2 In Monomentioning
confidence: 99%